Towards global elimination of lymphatic filariasis: a systematic review of the application of spatial epidemiological methods to enhance surveillance and support elimination programmes - Beatris Mario Martin (BMJ Publishing Group, 2024)
Background In recent decades, spatial epidemiology has increasingly been used to study neglected tropical diseases (NTDs). Spatial methods are particularly relevant when transmission is strongly driven by sociodemographic and environmental factors, resulting in heterogeneous disease distribution. We use lymphatic filariasis (LF)-an NTD targeted for global elimination-as a case study to examine how spatial epidemiology has been used to enhance NTD surveillance.Methods We conducted a systematic literature review of spatial analytical studies of LF published in English across PubMed, Embase, Web of Science and Scopus databases, before 15 November 2022. Additional papers were identified from experts' suggestions. Studies that employed spatial analytical methods were included, but those that applied only visualisation tools were excluded.Findings Sixty-one eligible studies published between 1997 and 2023 were identified. The studies used a wide range of spatial methods. Thirty-one (50.8%) studies used spatial statistical modelling, with model-based geostatistics being the most common method. Spatial autocorrelation and hotspot analysis were applied in 30 studies (49.2%). The most frequent model outputs were prevalence maps (17 studies, 27.9%), followed by risk maps based on environmental suitability (7 studies, 11.5%) and maps of the odds of seroprevalence being above a predetermined threshold (7 studies, 11.5%).Interpretation By demonstrating the applicability of spatial methods for investigating transmission drivers, identifying clusters and predicting hotspots, we highlight innovative ways in which spatial epidemiology has provided valuable evidence to support LF elimination. Spatial analysis is particularly useful in low-prevalence settings for improving hotspot detection and enhancing postelimination surveillance.PROSPERO registration number CRD42022333804.